Peranan pertubuhan sukarela wanita dalam pembangunan wanita di Sabah, 1963-2003 / Siti Aidah Lukin @ Lokin - Siti Aidah, Lukin @ Lokin (2017)
This study aims to analyse the roles of voluntary women organisations towards the development of women in Sabah from 1963 to 2003. The organisations focused in this study include Perkumpulan Perempuan Sabah (PPS), Pertubuhan Wanita Sabah (PEWASA), Sabah Women Action Resource Group/Kumpulan Daya Tindakan Wanita Sabah (SAWO) and Sabah Women Entrepreneurs and Professional Association (SWEPA). The establishment and development of voluntary women organisations in Sabah symbolise the progress achieved by the feminine population not only in the organisational activities but also in the socioeconomic field. These organisations offer women folks from different backgrounds the much needed opportunities to synergise their physical efforts and mental capacities in implementing programmes that assist them to develop and progress in society. This study examines the historical aspects of these voluntary women organisations, their development, and their activities. The vital roles of these organisations in bringing progress among the women can be observed and analysed via these activities. In line with the objectives of this study, the rich resources of these organisations and valuable private collections of individual outstanding women contributors and achievers were tapped during data collection. The findings reveal that these organisations not only function to create awareness of the importance of organisational skills and raising the status of women in Sabah but also to enable the government to implement developmental programmes among the women, particularly in the fields of economics, education, and health. In addition, this study provides the platform to identify and highlight issues faced by the women so that the government and other related agencies may know how to focus their efforts in developing the feminine community in Sabah. It is hoped that the new knowledge in this study can be a benefitial contribution towards research on women in Sabah history in particular and Malaysian history in general.